Análise de livros didáticos de inglês à luz dos documentos que norteiam os critérios de escolha de LDLI nas escolas públicas brasileiras - Souza, Luciane Garcia Gauthier de (2019)
This study aims to study the English textbooks adopted in Elementary School at the Military School of Santa Maria, considering the requirements in the documents of selection of textbooks for the English language. This research is a documentary analysis of qualitative approach. To carry out the research, we used the concept of multiliteracies according to the New London Group (1996); Soares (1998); Cope & Kalantzis (2000); Rojo (2012). The object of this study are the textbooks Uncover 1 and American English File 1. Data collection is done through a survey research and two documents: PNLD and PSD. The use of textbooks, both in public schools and private schools, is frequent in Brazil. However, in order to have an effective learning tool, teachers need to be able to choose the most appropriate textbook for their teaching practice context and for the changes our society has been going through. The Brazilian Textbook Program highlights that the textbooks need to follow the needs of the current school. The English Language Teaching Plans, created by the Brazilian Military School System and sent to the Military Schools, don’t guide in terms of textbook choices because the purpose of this document is to help teachers make their teaching plans for school year. Thus, we used the general guidelines from the English Language Teaching Plans and the competencies and abilities listed in the teaching plans in order to make a parallel with the criteria highlighted in the Guide of the Brazilian Textbook Program. After analyzing both textbooks Uncover 1 and American English File 1, we concluded that both meet the requirements of most of the 167 criteria distributed in 12 categories of the Guide of the Brazilian Textbook Program. The study showed that in both textbooks, 18 out of 167 criteria were not observed, 7 out of 167 were partially observed, and 10 out of 167 were observed in Uncover 1, but not in American English File 1. The suggestions we proposed for the choice of a textbook was based on the Military School teaching and pedagogical proposal, on the English Language Teaching Plans of the Brazilian Military School System and on the Brazilian Textbook Program. It aims to help guide the choice of a textbook, which is a decision that needs to be really coherent to the teaching practice context.